2019
DOI: 10.1111/ecog.04254
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal gradients of parasite richness: a review and new insights from helminths of cricetid rodents

Abstract: The latitudinal diversity gradient (LDG), or the trend of higher species richness at lower latitudes, has been well documented in multiple groups of free-living organisms. Investigations of the LDG in parasitic organisms are comparatively scarce. Here, I investigated latitudinal patterns of parasite diversity by reviewing published studies and by conducting a novel investigation of the LDG of helminths (parasitic nematodes, trematodes and cestodes) of cricetid rodents (Rodentia: Cricetidae). Using host-parasit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
61
3
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 138 publications
(288 reference statements)
2
61
3
4
Order By: Relevance
“…Qian, Fridley, and Palmer (2007) also found that z consistently decreased with increasing latitude for the North American flora, whereas Lyons and Willig (2002), using bats and marsupials of North and South America, found that z increased with latitude, while c exhibited a reverse pattern. Thus, despite the great interest of ecologists and biogeographers in latitudinal gradients (Fattorini & Ulrich, 2012; Lomolino, Riddle, Whittaker, & Brown, 2010; Preisser, 2019), it is not clear if and how z and c vary with latitude.…”
Section: Introductionmentioning
confidence: 99%
“…Qian, Fridley, and Palmer (2007) also found that z consistently decreased with increasing latitude for the North American flora, whereas Lyons and Willig (2002), using bats and marsupials of North and South America, found that z increased with latitude, while c exhibited a reverse pattern. Thus, despite the great interest of ecologists and biogeographers in latitudinal gradients (Fattorini & Ulrich, 2012; Lomolino, Riddle, Whittaker, & Brown, 2010; Preisser, 2019), it is not clear if and how z and c vary with latitude.…”
Section: Introductionmentioning
confidence: 99%
“…In total, we estimated 103,078 species of helminth parasites of vertebrates, most strongly represented by trematodes(44,262), followed by nematodes(28,844), cestodes(23,749), and acanthocephalans(6,223). Using an updated estimate of bony fish richness significantly increased these estimates from previous ones, with over 37,000 helminth species in this clade alone.Birds and fish were estimated to harbor the most helminth richness, but reptiles and amphibians had the highest proportion of undescribed diversity.…”
mentioning
confidence: 99%
“…In addition, climate is a strong correlate of species diversity for free-living organisms, especially at large spatial grains and extents (Field et al, 2009). Previous studies on parasites have also emphasized the prominence of climate as an important global predictor of parasite diversity (Dunn et al, 2010;Guernier et al, 2004;Preisser, 2019). Some proposed explanations for how climate affects species diversity are related to the speed of evolutionary processes, the amount of available energy and to species tolerances (see Currie et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…There is usually a strong correlation between species richness and climatic components leading to various hypotheses of how climate affects species diversity (Currie et al, 2004;Field et al, 2009). However, macroecological studies on parasite diversity are primarily focused on host-related drivers and latitudinal gradients (Poulin, 2014;Morand, 2015; but see Guernier et al, 2004;Preisser, 2019). Most studies found a positive association between host and parasite diversity regardless of host and parasite taxa (Kamiya et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation